Development of a condition‐specific patient‐reported outcome measure for measuring symptoms and appearance in vascular malformations: the OVAMA questionnaire. (14th June 2021) - Lokhorst, M.M.; Horbach, S.E.R.; Young‐Afat, D.A.; Stor, M.L.E.; Haverman, L.; Spuls, P.I.; van der Horst, C.M.A.M.; ,
Summary: Background: The symptoms and appearance of vascular malformations can severely harm a patient's quality of life. The aim of treatment of vascular malformations generally is to improve condition‐specific symptoms and/or appearance. Therefore, it is highly important to start testing treatment effects in clinical studies from the patient's perspective. Objectives: To develop a patient‐reported outcome measure for measuring symptoms and appearance in patients with vascular malformations. Methods: A first draft of the patient‐reported outcome measure was based on the previously internationally developed core outcome set. The qualitative part of this study involved interviews with 14 patients, which led to a second draft. The second draft was field tested cross‐sectionally, after which groups of items were evaluated for adequate internal consistency (Cronbach's alpha > 0·7) to form composite scores. Construct validity was evaluated by testing 13 predefined hypotheses on known‐group differences. Results: The patient interviews ensured adequate content validity and resulted in a general symptom scale with six items, a head and neck symptom scale with eight items, and an appearance scale with nine items. Cronbach's alpha was adequate for two composite scores: a general symptom score (0·88) and an appearance score (0·85). Ten out of 13 hypotheses on known‐group differences were confirmed, confirming adequate construct validity. Conclusions: With the development of the OVAMA questionnaire, outcomes of patients with vascular malformations can now be evaluated from the patient's perspective. This may help improve the development of evidence‐based treatments and the overall care for patients with vascular malformations. Abstract : What is already known about this topic? The symptoms and appearance of vascular malformations may severely impact the patient's physical, mental and social functioning. Condition‐specific symptoms and appearance are the main drivers for treatment of vascular malformations. Symptoms and appearance were determined to be core outcome domains and should be measured in all clinical research on vascular malformations. No instrument exists for measuring patient‐reported symptoms and appearance problems in vascular malformations. Vascular malformation research is hampered by heterogeneity in outcome measures. What does this study add? With this study, a condition‐specific patient‐reported outcome measure was developed for measuring symptoms and appearance in patients with vascular malformations: the OVAMA questionnaire. This study confirms adequate content and construct validity. What are the clinical implications of this work? The problems that matter most to patients with vascular malformations can now be evaluated from the patient's perspective. Treatments can be evaluated and compared for effects on these core outcome domains. This study is a big step in tackling current heterogeneity in outcome measures. Clinically distinct groups can be determined based on disease severity. The many applications of the OVAMA questionnaire may significantly improve research and, ultimately, the care for patients with vascular malformations. Linked Comment:  J. Tan. Br J Dermatol 2021; 185 :695–696 .